Physiological Response of Upland Rice Varieties to Furrow with Organic Matter on Agroforestry System with Kayu Putih (Melaleuca leucadendra L.) - Puji Lestari Tarigan; Tohari Tohari; Priyono Suryanto (Caraka Tani: Journal of Sustainable Agriculture, 2019)
Drought is one of the major limitations in dry land cultivation. Drought affects plant physiology processes such as photosynthesis, respiration, mineral and water transportation, and transpiraton, briefly called drought stress. Drought stress can be avoided by managing environment. Furrow containing organic matter for rain fed rice has been the subject of many studies, with special emphasis on soil moisture. This research is aimed to know the effects of the furrow containing organic matter on physiological responses of several upland rice varieties on agroforestry system based on kayu putih (cajuput). The experimental design applied the strip plot design. The vertical factor is the furrow system of treatment consisting of 2 levels i.e. without furrow + without organic matter and furrow + organic matters. The horizontal factors are the upland rice varieties consisting of 3 varieties i.e. Situ Patenggang, Situ Bagendit and Ciherang. The collected data were analyzed by Analysis of Variance (ANOVA) applying a level of significance α = 5%. Whenever significant differences among treatments were found, further analysis was carried out by applying the Tukey's HSD (Honestly Significant Difference) test α = 5% levels. The result shows that drought affects plant physiology and can be avoided by using furrow containing organic matters. Situ Patenggang with furrow containing organic matters has the higher physiology capability, it had photosynthesis 387.18 µmol CO2 per clump s-1, transpiration 3038.50 mg per clump per secondand CO2 721.11 mol CO2 clump per mol. There different plant requirements for Cu between varieties.